D. Álvaro Pelayo O. Min. y D. Alfonso IV de Portugal y las relaciones de Poder - C. R. de Souza, José Antônio de (Anales del Seminario de Historia de la Filosofía, 2003)
Designated bishop of Silves, diocese of Faro, Algarve, in 1334, D. Alvaro Pelayo entered in conflict with Alfonso IV (1325-57), the King of Portugal, sending him two letters in that one can notice that there he also had to defend the jurisdictional autonomy of the spiritual power, in order to the centralizing politics that the king, following his father’s steps, D. Dinis (1279-1325), gave continuity, with the purpose of restricting the political space of the high Lusitanian clergy. Past some few years, (1347) for the same reason, the conflict of the relationships of power among the two authorities increased. Our purpose here is double: to analyze the historical facts related with the two mentioned conflicts, well as the aspects doctrinal contents in the two referred letters, with view to show the thought coherence and attitude of D. Alvaro Pelayo.